O efeito devolutivo da apelação criminal e a fundamentação das decisões: estudo sobre a possibilidade de complementação da fundamentação no julgamento de apelação exclusiva da defesa - Barbosa, Guilherme Diniz (2021)
The main objective of the present work was to investigate the possibility of the competent court for judgment of the appeal complement the statement of reasons of the first instance decision, specifically regarding the definition of the punishment and in the hypothesis in which only the defense appeals. The answer to this question was sought by taking the constitutional criminal procedure as a parameter, as outlined in the 1988 Brazilian Constitution, the American Convention on Human Rights and the International Covenant on Civil and Political Rights, which is destined to limit the state’s punitive power. It was necessary to expose the existing disparity between constitutional and conventional regulations and judicial practice in Brazil, supported by theories that contribute to the permanence of the authoritarian model that inspired the 1941 Code of Criminal Procedure, causing the weakening of procedural guarantees. To check the compatibility of complementing the reasoning in the judgment of the defense's appeal with the constitutional criminal process, an analysis was carried out of the judicial duty to give reasons and the defendant's right to appeal, in order to present its current contours. In the Democratic State of Law, there is an indissoluble connection between the contradictory principle and the judicial duty to give reasons, given the fact that the process is a space for citizen participation in state decisions. Reasoning and the right to appeal are presented as guarantees capable of reducing the spaces of judicial discretion, enabling the containment of arbitrariness, which becomes essential in the matter of defining the punishment, given the wide freedom granted to the judge by the Penal Code. The research carried out in judgments of the Superior Court of Justice (STJ) and the Federal Supreme Court (STF) indicated that these Courts understands that the devolutive effect of the appeal would allow the complementation of the reasoning, without violating the prohibition of reformatio in pejus. Thus, it was developed a critical examination of this position based on a redefinition of the devolutive effect of the appeal according to the constitutional criminal process, demonstrating the incompatibility of this procedure with a democratically based process